Body Size of Wood Ant Workers Affects their Work Division - Adam Véle; Roman Modlinger (Sociobiology, 2019)
The division of functions among ant workers and their mutual cooperation is one of the reasons for ants’ success. The activities that workers perform in the nest can be divided by age or morphology. We studied the body size of workers of the wood ant Formica polyctena as a function of their activity. Our results show that workers exploiting protein baits were larger than workers attracted to carbohydrate baits. The biggest of all were workers located at the upper parts of the nest, which shows the importance of nest defense and maintenance. It also points that the distribution of functions does not have to be given only by workers age. Work division based on several mechanisms may be advantageous for colony functioning.